Modeling of riveted assembly of wing sheathing with forward stiffeners - Bormotin, K.S.; Oleinikov, A.I.; Ovcharov, I.O. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2015)
Modeling of a high-reliability riveted joint of a double-curvature panel with ribbed stiffeners is considered. A mathematical formulation of the problem devoted to riveting the joints of panels and stiffeners is given. An iterative method of determining the forward curvatures of stiffeners that provide the prescribed geometrical parameters of riveted panels is proposed. This method is implemented using the MSC.Marc and MSC.Patran finite-element analysis software packages.